2017
DOI: 10.1186/s13293-017-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in endogenous cortical network activity: spontaneously recurring Up/Down states

Abstract: BackgroundSeveral molecular and cellular processes in the vertebrate brain exhibit differences between males and females, leading to sexual dimorphism in the formation of neural circuits and brain organization. While studies on large-scale brain networks provide ample evidence for both structural and functional sex differences, smaller-scale local networks have remained largely unexplored. In the current study, we investigate sexual dimorphism in cortical dynamics by means of spontaneous Up/Down states, a type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…the main finding of this study), one cannot exclude this possibility if a larger sample is analyzed. This is of particular importance since a previous report has found differences in LFPs recorded from the somatosensory cortex of male or female mice 49 . Further studies specifically comparing larger samples of male or female mice in adulthood will be required to consolidate the findings of the present exploratory study.…”
Section: Discussionmentioning
confidence: 87%
“…the main finding of this study), one cannot exclude this possibility if a larger sample is analyzed. This is of particular importance since a previous report has found differences in LFPs recorded from the somatosensory cortex of male or female mice 49 . Further studies specifically comparing larger samples of male or female mice in adulthood will be required to consolidate the findings of the present exploratory study.…”
Section: Discussionmentioning
confidence: 87%
“…Most investigations on aging were conducted with the C57BL strain [ 28 , 65 , 72 , 82 , 102 , 103 , 115 , 117 ] while a few studies investigated other strains, e.g., DBA/2J [ 28 ], the wild type from Tg2576 [ 43 ], or CBA/J [ 83 ]. Age-related changes in sleep EEG have been observed (see below), albeit they differ slightly among strains [ 28 , 41 ].…”
Section: Age-related Effects On Sleep Electrophysiology In Micementioning
confidence: 99%
“…Furthermore, almost all studies except for one [ 43 ] investigated male mice. Sleep in both sexes was analyzed and compared only once by Sigalas and colleagues [ 102 ]. In general, measured sleep parameters across research groups are less consistent than in human research; thus, degree of generalization is lower.…”
Section: Age-related Effects On Sleep Electrophysiology In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Here we have examined the effect of chemically induced ELS on the endogenous cortical activity in brain slices from mouse cortex. Previous studies, including our own have shown that local recurrent networks formed by excitatory and inhibitory connectivity in the neocortex generate stable and self-sustaining periods of persistent activity alternating with periods of no activity, called Up and Down states, respectively – a prominent feature of the cortical activity during slow wave sleep in vivo ( Steriade et al, 1993 , 2001 ; Sanchez-Vives and McCormick, 2000 ; Cossart et al, 2003 ; MacLean et al, 2005 ; Haider et al, 2006 ; Rigas and Castro-Alamancos, 2007 , 2009 ; Poulet and Petersen, 2008 ; Rigas et al, 2015 ; Sigalas et al, 2015 , 2017 ). Such activity is maintained in cortical slice preparations, in the absence of sensory inputs or active neuromodulation, indicating that it is chiefly the outcome of intrinsic properties of local networks and hence reflects the ‘default’ activity of the cortex ( Yuste et al, 2005 ; Sanchez-Vives et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%